Keragu-raguan terhadap Agama: Wacana Humanisme dan Eksistensialisme - Mawardi Mawardi (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2013)
Religion has a significant role on people‟s lives. So the community is very  important to attend and maintain their religious life. Society does not need to  create a “new religion” to address issues of human life. When people lose grip  norms that make life not worth , religion will serve as a protective ceiling in  various approaches and views. Each of these disciplines to define and view  religion in their own way according to his interests. This can be seen for instance  from view of religion given by the flow of humanism and existentialism.